Dynamic stress response of saturated soil subjected to vertical and horizontal moving loads inside a circular tunnel. (July 2018) - Zhou, Shunhua; Di, Honggui; Luo, Zhe; He, Chao; Zhang, Xiaohui
This study proposed an improved tunnel model for the evaluation of dynamic stress of the saturated soil subjected to vertical and horizontal moving loads. Based on this model, the response of dynamic stress of the saturated soil subjected to three typical loading scenarios is systematically analysed: (1) vertical moving loads, (2) combined vertical moving load and longitudinal horizontal load due to the braking of a train, and (3) combined vertical moving load and tangential horizontal load during the turning of a train at small curved sections. The simulated results reveal that soil permeability, load speed and load frequency have a significant influence on the dynamic stress of the saturated soil. The two types of horizontal loads have considerable effects on the shear stress but have negligible influence on the normal stress and pore-water pressure of the saturated soil.